(untitled) (Al-Farooq Journal of Sciences, 2026)
The increasing adoption of mobile healthcare applications has transformed how patients access healthcare services, communicate with healthcare providers, and schedule medical appointments. Despite these advancements, older adults often encounter challenges when interacting with healthcare applications due to age-related changes in vision, memory, motor skills, and limited familiarity with digital technologies. Voice-enabled interfaces have emerged as a promising approach to improve accessibility and simplify user interaction. This study presents the design and usability evaluation of a voice-enabled healthcare appointment booking prototype developed specifically for older adults in Libya. The prototype was designed using Figma and incorporated a conceptual voice interaction mechanism intended to support appointment scheduling through a simplified interaction process. A usability evaluation was conducted involving eleven participants aged 50 years and above. Data were collected using a structured questionnaire that assessed ease of use, interface clarity, user understanding, interaction preferences, and perceived usefulness. The findings indicate that 81.8% of participants considered the prototype easy or very easy to use, while 90.9% reported that the interface elements were clear and understandable. Most participants completed the interaction process without significant difficulties. Although participants did not exclusively prefer voice interaction, many expressed interest in combining voice and touch-based interaction methods. The study demonstrates the potential of voice-enabled design concepts to improve healthcare accessibility for older adults and provides preliminary evidence supporting the future development of voice-oriented healthcare applications within the Libyan context.